2011
DOI: 10.1371/journal.pone.0022345
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid-Induced Ultra-Weak Photon Emission from Chlamydomonas reinhardtii as a Tool for Monitoring of Lipid Peroxidation in the Cell Membranes

Abstract: Reactive oxygen species formed as a response to various abiotic and biotic stresses cause an oxidative damage of cellular component such are lipids, proteins and nucleic acids. Lipid peroxidation is considered as one of the major processes responsible for the oxidative damage of the polyunsaturated fatty acid in the cell membranes. Various methods such as a loss of polyunsaturated fatty acids, amount of the primary and the secondary products are used to monitor the level of lipid peroxidation. To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 53 publications
3
32
0
Order By: Relevance
“…It has been previously reported that the intensity of ultra-weak photon emission is determined by the cell density, the level of oxidative metabolic processes and pigment content682324. The cell density in petri-plate containing solid media composed of agar is typically by several orders lower than the cell density in plant and animal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that the intensity of ultra-weak photon emission is determined by the cell density, the level of oxidative metabolic processes and pigment content682324. The cell density in petri-plate containing solid media composed of agar is typically by several orders lower than the cell density in plant and animal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decades, one-dimensional detection of ultra-weak photon emission was performed using low-noise photomultiplier tube (PMT)5678. Current development in highly sensitive charge coupled device (CCD) camera allows two-dimensional imaging of spontaneous ultra-weak photon emission.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Under Cd stress, photon emissions by the non-primed leaves were higher than those of BABA-primed leaves, indicating that non-primed leaves experienced more oxidative damage. An ultra-weak photon emission measurement system has been successfully used as a non-invasive tool for monitoring membrane lipid peroxidation in Chlamydomonas [56]. Moreover, the optical detection of responses to salinity and drought stress using a biophoton technique has been documented in red beans [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The study done by Ankush Prasad and Pave Pospısil revealed that the oxidation of linoleic acid by hydroxyl radical and intrinsic lipoxygenase results in the ultraweak photon emission (Prasad and Pospısil 2011).…”
Section: What Is the Logic Of Bio-energy Methods?mentioning
confidence: 99%